2022
DOI: 10.1177/17446295221095712
|View full text |Cite
|
Sign up to set email alerts
|

Remote cognitive training for children with congenital brain malformation or genetic syndrome: a scoping review

Abstract: Increased attention is arising on the delivery of remote cognitive interventions, which allow performing exercises in everyday settings, favouring rehabilitation continuity. The present study offers an overview of remote cognitive training programs for children with congenital brain malformation or genetic syndrome affecting the central nervous system, included in papers published in the time period 2011-2021. A total of 13 records was found and discussed including efficacy studies, feasibility studies and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 81 publications
0
3
1
Order By: Relevance
“…This data is conflicting with previous studies suggesting that patients with CBM frequently show a complex clinical picture characterized by behavioral and physical issues together with low intellectual abilities, which may lead to limited possibilities to obtain significant gains from a remote training 6 . In addition, previous studies showed that the important difficulties of these children could even hamper the possibility of performing a remote training, suggesting that telerehabilitation may be a viable option only for a limited subgroup of children 76 , 77 .…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…This data is conflicting with previous studies suggesting that patients with CBM frequently show a complex clinical picture characterized by behavioral and physical issues together with low intellectual abilities, which may lead to limited possibilities to obtain significant gains from a remote training 6 . In addition, previous studies showed that the important difficulties of these children could even hamper the possibility of performing a remote training, suggesting that telerehabilitation may be a viable option only for a limited subgroup of children 76 , 77 .…”
Section: Discussioncontrasting
confidence: 78%
“…A total of 40 sessions had to be performed by each participant, with a commitment of 5 times per week in a total period of 8 weeks. The intensity and duration of this version of Lumosity Cognitive Training were chosen on the basis of the characteristics of previous CCT programs for pediatric populations with brain damage or neurodevelopmental disorders 3 , 6 , 41 , 86 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations